Credibility and Nominal Debt : Exploring the Role of Maturity in Managing Inflation. (IMF Working Papers; Working Paper ;, 1989)
This paper focuses on the role of debt maturity in managing the government's incentives to use opportunistic inflation to reduce the ex post real value of its nominal liabilities. The maturity structure of government debt is shown to be a powerful instrument to affect the time profile of the inflation tax base and, hence, to mitigate the distortions introduced by time inconsistency on taxation policies. The nature of the optimal policy is shown to be heavily dependent on the type of precommitment enjoyed by policymakers.